BENFORD'S LAW AND ITS APPLICATION - Jasak, Zoran (ACADEMIC REVIEW, 2021)
Subject of this paper is Benford's law, statistical characteristics of big data sets. Goal is to introduce users with basic properties and advantages of this law, having in mind relatively low level of knowledge about this law and of possibilities its practical and theoretical application on our region. Benford's law is logarithmic law which describes dynamics of leading digits in big data sets. It's detected 140 years ago, but expansion of practical use has started by development of computer technique, particularly of personal computers. There is almost no area of human activity and science in which possibility of it's application is not detected. Benford's law became one of key tools for detection of financial frauds, and anomalies of any kind as well.